TQ-Ox, a novel synthetic derivative of thymoquinone on ovarian cancer cells in vitro - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2022)
© 2022 Informa UK Limited, trading as Taylor & Francis Group.There are many studies in the literature on thymoquinone (TQ)-related cancer cells and models, and there is no relevant study investigating the efficacy of the oxime derivative of TQ (TQ-Ox). This study synthesized TQ-Ox and examined its cytotoxic, genotoxic and apoptotic properties in ovarian cancer cells. The structure TQ-Ox was confirmed with NMR. The cytotoxicity by luminometric ATP, intracellular reactive oxygen species (iROS) by fluorometric, intracellular calcium (iCa2+) by fluorometric, mitochondrial membrane potential (MMP) by flow cytometry, glutathione (GSH) levels with GSH/GSSG-Glo assay, DNA damage by comet assay, and apoptosis by acridine orange/ethidium bromide dye were determined. Concentrations of TQ-Ox were statistically increased cytotoxicity, DNA damage, apoptosis, iROS, and iCa2+ in a concentration-dependent manner (p < 0.001). Besides, MMP and GSH levels also decreased statistically significantly (p < 0.001) with increasing concentrations. TQ-Ox would be an effective treatment option by increasing cytotoxicity, genotoxicity, and apoptosis in ovarian carcinoma.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bitki ve Hayvan Bilimleri; BİTKİ BİLİMLERİ; KİMYA, ANALİTİK; KİMYA, ORGANİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Agriculture & Environment Sciences (AGE); Natural Sciences (SCI); Life Sciences (LIFE); PLANT & ANIMAL SCIENCE; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PLANT SCIENCES; CHEMISTRY, ANALYTICAL; CHEMISTRY, ORGANIC; BIOCHEMISTRY & MOLECULAR BIOLOGY; Fizik Bilimleri; Bitki Bilimi; Organik Kimya; Physical Sciences; Plant Science; Organic Chemistry; Apoptosis; genotoxicity; ovarian cancer; thymoquinone-oxime